Conception and pregnancy rates in dairy cows after various programmed breeding systems - Stevenson, Jeffrey S.; Thompson, K. E.; Kobayashi, Y. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Two experiments were conducted to measure conception and pregnancy rates in lactating dairy cows after various treatments followed by artificial insemination (AI) after detected estrus or at one fixed time. In Experiment 1, Holstein cows in one herd were assigned randomly to four treatments every 3 wk (27, 3-wk cluster groups): 1)Ovsynch33, 2) GnRH+PGF[subscript]2alpha, 3) 2xPGF[subscript]2alpha, and 4) 2xPGF[subscript]2alpha+GnRH. In Experiment 2, Holstein cows in one herd were assigned randomly to two treatments every 3 wk (14, 3-wk cluster groups): 1) Ovsynch48 and 2) GnRH+PGF[subscript]2alpha. In both experiments, frozen-thawed semen from multiple sires was used, one technician performed >95% of all inseminations, and pregnancy was diagnosed by palpation per rectum between 38 and 52 d after first insemination. Although actual conception rates resulting from inseminations after detected estrus were consistently greater, pregnancy rates of cows were superior after fixed-time inseminations because of poor rates of detected estrus in treatments that relied solely on observation of sexual behavior.
Keywords: OvSynch; Synchronized estrus; Conception; Pregnancy rates